Laminate, molded article, and method for manufacturing laminate

By using a specific ratio of poly(3-hydroxybutyrate) resin and a resin layer of less than 90 mole % saponification polyvinyl alcohol on the paper substrate, the adhesiveness of the coated paper during the heat sealing process is solved. The problems of insufficient and insufficient water resistance have achieved high levels of adhesion and water resistance, and are suitable for the production of paper containers such as paper tableware.

CN119278129APending Publication Date: 2025-01-07KANEKA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380043693.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-05-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing coating paper lacks adhesion during the heat sealing process, which leads to the easy peeling of the coating layer, and the performance is insufficient when used for paper containers with high-level water resistance requirements, which cannot meet the long-term water resistance requirements of warm water.

Method used

A resin layer containing poly(3-hydroxybutyrate) resin is formed on a paper substrate, and a saponification degree polyvinyl alcohol of less than 90 mole % is formed by forming a solid component weight ratio of 99.8/0.2 to 95.0 with a specific ratio of 99.8/0.2 to 95.0. Resin layer improves adhesion and water resistance.

Benefits of technology

It realizes good adhesion and water resistance on paper substrates, can heat seal at a lower heating temperature, is suitable for molding into paper containers such as paper tableware, and demonstrates long-term water resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

A laminate includes a paper substrate layer and a first resin layer provided on at least one surface of the paper substrate layer. The first resin layer contains a poly (3-hydroxybutyrate)-based resin and a polyvinyl alcohol having a degree of saponification of less than 90 mol%. The solid content weight ratio of the poly (3-hydroxybutyrate)-based resin to the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.0. The laminate can be produced by applying an aqueous coating liquid to at least one surface of a paper substrate and drying the same to form a first resin layer on the paper substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate having a resin layer containing a poly(3-hydroxybutyrate)-based resin, and a molded product containing the laminate. Background Art

[0002] In recent years, environmental issues caused by discarded plastics have attracted much attention. In particular, marine pollution caused by discarded plastics is serious, and there is a great demand for the popularization of biodegradable resins that can be decomposed in the natural environment.

[0003] Various resins are known as such biodegradable resins, among which poly(3-hydroxybutyrate)-based resins are thermoplastic polyesters produced and accumulated as energy storage materials in the cells of many microbial species. Since they are biodegradable not only in soil but also in seawater, they have attracted attention as raw materials for solving the above-mentioned problems.

[0004] A laminate formed by laminating a layer containing a poly(3-hydroxybutyrate)-based resin on a biodegradable paper substrate is very promising from the viewpoint of environmental protection because both the resin and the substrate are materials with excellent biodegradability.

[0005] As an example of such a laminate, Patent Document 1 describes a coated paper having a coating layer on a paper substrate in order to reduce coating defects, wherein the coating layer contains poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) which is a type of poly(3-hydroxybutyrate)-based resin and an adhesive such as polyvinyl alcohol at a specific ratio.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2021 / 256381 Summary of the invention

[0009] Problems to be solved by the invention

[0010] The coated paper described in Patent Document 1 has a certain degree of water resistance and heat sealability, but there is a tendency that the coating layer is easily peeled off from the paper substrate due to insufficient adhesion between the coating layer and the paper substrate. Therefore, for example, good heat sealability may not be achieved by the heating conditions during heat sealing.

[0011] When the coated paper is molded into a paper container such as paper tableware for use, a high level of water resistance (for example, resistance to warm water for a long period of time) may be required. However, Patent Document 1 does not take such a high level of water resistance into consideration.

[0012] In view of the above-mentioned current situation, an object of the present invention is to provide a laminate having a resin layer containing a poly(3-hydroxybutyrate)-based resin on a paper substrate and having both good adhesiveness and water resistance.

[0013] Solutions to the problem

[0014] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by adding polyvinyl alcohol having a specific saponification degree to a resin layer containing a poly(3-hydroxybutyrate) resin at a specific ratio, thereby completing the present invention.

[0015] That is, the present invention relates to a laminate comprising: a paper substrate layer, and a first resin layer provided on at least one side of the paper substrate layer, wherein the first resin layer contains a poly(3-hydroxybutyrate)-based resin and a polyvinyl alcohol having a saponification degree of less than 90 mol %, and the solid content weight ratio of the poly(3-hydroxybutyrate)-based resin / the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.0.

[0016] In addition, the present invention also relates to a method for manufacturing a laminate, which includes: applying an aqueous coating liquid to at least one side of a paper substrate, drying it, and forming a first resin layer on the paper substrate; the aqueous coating liquid contains a poly (3-hydroxybutyrate) resin and a polyvinyl alcohol having a saponification degree of less than 90 mol%, and the solid content weight ratio of the poly (3-hydroxybutyrate) resin / the polyvinyl alcohol is 99.8 / 0.2~95.0 / 5.0.

[0017] Effects of the Invention

[0018] According to the present invention, there can be provided a laminate having a resin layer containing a poly(3-hydroxybutyrate)-based resin on a paper substrate and having both good adhesiveness and water resistance.

[0019] The laminated body of the preferred embodiment exhibits long-term water resistance to hot water and can be molded into a paper container such as paper tableware and used.

[0020] The laminated body according to the preferred embodiment can exhibit good heat-sealing properties even when heat-sealed at a relatively low heating temperature.

[0021] In addition, the laminated body according to another embodiment further includes a second resin layer, and the adhesion (laminating property) between the paper base layer and the second base layer is good. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.

[0023] [Laminated body]

[0024] A laminate according to one embodiment of the present disclosure includes at least a paper base layer and a first resin layer laminated on one or both surfaces of the paper base layer. The laminate exhibits biodegradability as a whole.

[0025] The first resin layer may be directly laminated on the paper base layer or laminated via another layer, but is preferably laminated directly.

[0026] In one embodiment of the present disclosure, the first resin layer may be the outermost layer on the laminate, and in this case, the first resin layer may function as a heat seal layer, a water resistant layer, and / or an oil resistant layer.

[0027] In another embodiment of the present disclosure, other layers may be stacked on the first resin layer. In this case, the first resin layer may function as an adhesion-promoting coating layer between the paper substrate layer and the other layers. The other layers are not particularly limited and may be resin layers or inorganic layers. As an example, the second resin layer described below may be cited.

[0028] The surface of the paper base layer opposite to the side on which the first resin layer is laminated may be the outermost layer, or may be laminated with a plurality of layers. The layer may be a layer corresponding to the first resin layer or a layer other than the first resin layer.

[0029] (Paper base material layer)

[0030] The paper base material layer is mainly composed of a sheet made of pulp. The paper base material can be obtained by making paper from a papermaking raw material containing a filler, various auxiliary agents, etc. in pulp.

[0031] The type of paper substrate that can be used is not particularly limited, and examples thereof include cup wax paper, kraft paper, full pulp paper, coated paper, thin paper, cellophane, and cardboard.

[0032] The pulp is not particularly limited, and examples thereof include chemical pulps such as bleached kraft hardwood pulp (LBKP), bleached kraft softwood pulp (NBKP), unbleached kraft hardwood pulp (LUKP), unbleached kraft softwood pulp (NUKP), and sulfite pulp; mechanical pulps such as stone-ground pulp and thermomechanical pulp; wood fibers such as deinked pulp and waste paper pulp; and non-wood fibers obtained from kenaf, bamboo, hemp, and the like. These can be used in combination as appropriate.

[0033] Among them, chemical pulp and mechanical pulp made of wood fiber are preferably used, and chemical pulp is more preferably used, because it is difficult for impurities to be mixed into the paper base material, it is difficult to discolor over time when recycled as a waste paper raw material, the surface feeling during printing becomes good due to high whiteness, and the use value when used as a packaging material is increased. Specifically, the blending amount of chemical pulp such as LBKP and NBKP in the pulp is preferably 80% or more, and the blending amount of chemical pulp is particularly preferably 100%.

[0034] There is no particular limitation on the filler, and examples thereof include: inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silicon dioxide, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate; and organic fillers such as urea-formaldehyde resin, polystyrene resin, phenolic resin, and tiny hollow particles. It should be noted that the filler is not an essential material and may not be used.

[0035] The various auxiliary agents are not particularly limited, and examples thereof include sizing agents such as rosin, alkyl ketene dimer (AKD), and alkenyl succinic anhydride (ASA); dry paper strengthening agents such as polyacrylamide-based polymers, polyvinyl alcohol-based polymers, cationic starch, various modified starches, urea-formaldehyde resins, melamine-formaldehyde resins, wet paper strengthening agents, retention aids ( ), filter aid, coagulant, aluminum sulfate, bulking agent ( ), dyes, fluorescent brighteners, pH adjusters, defoamers, UV inhibitors, anti-fading agents, strength control agents ( ), slime control agent, etc. These can be appropriately selected and used as needed.

[0036] The surface of the paper substrate can be treated with various chemical agents. The chemical agent is not particularly limited, and examples thereof include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agent, water-resistance agent, water-retaining agent, thickener, lubricant, etc. As the chemical agent, only one kind can be used, or two or more kinds can be used in combination. In addition, these chemical agents can be used in combination with pigments.

[0037] The pigment is not particularly limited, and examples thereof include kaolin, clay, special kaolin, layered clay ( ), heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate, colloidal silica, satin white and other inorganic pigments; dense type, hollow type, or core-shell type organic pigments, etc. As the pigment, only one kind may be used, or two or more kinds may be used in combination.

[0038] The basis weight of the paper substrate can be appropriately selected according to the desired quality and the application of the laminate, and is usually preferably 20 g / m 2 Above and 600g / m 2 Below, more preferably 25g / m 2 Above and 600g / m 2 When the laminate is used for packaging materials such as wrapping paper, paper bags, lidding materials, floor coverings, soft packaging materials, posters for outdoor use, etc., 30 g / m 2 Above and 150g / m 2 It should be noted that the soft packaging material refers to the packaging material, especially the one using 30g / m 2 ~100g / m 2 When the laminate is used for paper cups, paper boxes, paper plates, paper trays and other paper containers, the weight is preferably 150 g / m 2 Above and 300g / m 2 the following.

[0039] The density of the paper substrate can be appropriately selected according to the desired quality and handling properties, and is usually preferably 0.5 g / cm 3 Above and 1.0g / cm 3 the following.

[0040] The method for making the paper substrate (papermaking) is not particularly limited, and can be appropriately selected from known papermaking machines such as a fourdrinier papermaking machine, a cylinder papermaking machine, a short-net papermaking machine, a gap former type, a hybrid former type (on-top former type) and the like. The pH during papermaking can be any one of an acidic range (acidic papermaking), a suspected neutral range (suspicious neutral papermaking), a neutral range (neutral papermaking), and an alkaline range (alkaline papermaking). It is also possible to apply an alkaline chemical agent to the surface of the paper layer after papermaking in the acidic range. In addition, the paper substrate can be composed of one layer or multiple layers of more than two layers.

[0041] When the surface of the paper substrate is treated with a chemical agent, the surface treatment method is not particularly limited, and a metering rod sizing machine ( )、Pond type sizing machine( ), door panel roller coater, sprayer, blade coater, curtain coater and other well-known coating devices.

[0042] (First resin layer)

[0043] The first resin layer provided on at least one side of the paper substrate layer contains at least a poly(3-hydroxybutyrate) resin and polyvinyl alcohol having a specific degree of saponification. The resin component contained in the first resin layer may be only the poly(3-hydroxybutyrate) resin and the polyvinyl alcohol, or may further contain another resin. As the other resin, a biodegradable resin described below may be used.

[0044] The first resin layer preferably contains 50% by weight or more of a poly(3-hydroxybutyrate) resin (hereinafter, sometimes referred to as P3HB), more preferably 70% by weight or more, further preferably 80% by weight or more, and further preferably 90% by weight or more. The first resin layer contains the poly(3-hydroxybutyrate) resin as a main component, and thus can exhibit biodegradability, particularly seawater degradability.

[0045] P3HB refers to a homopolymer having a 3-hydroxybutyrate unit and / or a copolymer containing a 3-hydroxybutyrate unit and other hydroxyalkanoate units. From the viewpoint of seawater degradability, a copolymer containing a 3-hydroxybutyrate unit and other hydroxyalkanoate units is preferred.

[0046] The hydroxyalkanoic acid constituting the copolymer is not particularly limited, and examples thereof include 4-hydroxybutyric acid, 3-hydroxypropionic acid, 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, and 3-hydroxyoctanoic acid, in addition to 3-hydroxybutyric acid.

[0047] Specific examples of P3HB include poly(3-hydroxybutyrate) (abbreviation: PHB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviation: PHBH), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviation: P3HB3HV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviation: P3HB4HB), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate) (abbreviation: P3HB3HO), poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate) (abbreviation: P3HB3HOD), poly(3-hydroxybutyrate-co-3-hydroxydecanoate) (abbreviation: P3HB3HD), poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) (abbreviation: P3HB3HV3HH), etc. Among them, PHB, PHBH, P3HB3HV, and P3HB4HB are preferred from the viewpoint of ease of industrial production.

[0048] Among them, PHBH is particularly preferred from the viewpoint that the melting point and crystallinity can be changed by changing the composition ratio of the repeating units, and as a result, physical properties such as Young's modulus and heat resistance can be changed, and physical properties between those of polypropylene and polyethylene can be imparted, and PHBH is easy to produce industrially and is a plastic useful in terms of physical properties.

[0049] The first resin layer preferably contains 50 wt% or more of PHBH, more preferably 70 wt% or more, further preferably 80 wt% or more, and further preferably 90 wt% or more. The resin components contained in the first resin layer may be only PHBH and the above-mentioned polyvinyl alcohol, or may further contain other resins.

[0050] As resins other than PHBH and the above-mentioned polyvinyl alcohol, P3HB other than PHBH can be cited. In addition, biodegradable resins other than P3HB include aliphatic polyester resins such as polycaprolactone, polybutylene adipate succinate, polybutylene succinate, and polylactic acid, and aliphatic aromatic polyester resins such as polybutylene terephthalate adipate and polybutylene terephthalate azelate.

[0051] A specific method for producing PHBH is described in, for example, International Publication No. 2010 / 013483. Commercially available products of PHBH include "KANEKA Biodegradable Polymer Green Planet" (registered trademark) manufactured by Kaneka Corporation.

[0052] The average content ratio of each constituent monomer in PHBH is preferably 3HB / 3HH=97~75 / 3~25 (mol% / mol%), and more preferably 3HB / 3HH=94~82 / 6~18 (mol% / mol%). When the average content ratio of 3HH in PHBH is 3 mol% or more, good adhesion can be obtained by heat sealing. In addition, the crystallization rate of PHBH with an average content ratio of 3HH of less than 25 mol% does not become too slow, and it is relatively easy to manufacture.

[0053] The PHBH having an average 3HH content of 3 to 25 mol % may be composed of one type of PHBH, a mixture of at least two types of PHBH having different content ratios of constituent monomers, or a mixture of at least one type of PHBH and PHB.

[0054] It should be noted that the average content ratio of each constituent monomer in PHBH can be obtained by a method known to those skilled in the art, for example, by the method described in paragraph

[0047] of International Publication No. 2013 / 147139 or by NMR measurement. The above average content ratio refers to the molar ratio of 3HB and 3HH in the entire PHBH contained in the first resin layer. When PHBH is a mixture containing at least two types of PHBH, or a mixture containing at least one type of PHBH and PHB, the above average content ratio refers to the molar ratio of each monomer contained in the entire mixture.

[0055] The weight average molecular weight (hereinafter sometimes referred to as Mw) of P3HB contained in the first resin layer can be appropriately selected, but from the viewpoint of both mechanical properties and processability, it is preferably 50,000 to 700,000, more preferably 100,000 to 600,000, and further preferably 150,000 to 550,000. When the weight average molecular weight of P3HB is 50,000 or more, the mechanical properties become good; when it is 700,000 or less, good adhesion can be obtained by heat sealing.

[0056] The weight average molecular weight of the above-mentioned P3HB can be determined as a molecular weight in terms of polystyrene by gel permeation chromatography (GPC) ("Shodex GPC-101" manufactured by Showa Denko K.K.) using a polystyrene gel ("Shodex K-804" manufactured by Showa Denko K.K.) in a column and chloroform as a mobile phase.

[0057] (Polyvinyl alcohol)

[0058] The first resin layer contains polyvinyl alcohol (hereinafter sometimes referred to as PVA) in addition to P3HB. By containing PVA in the first resin layer, the adhesion between the paper base material layer and the first resin layer can be improved.

[0059] PVA is generally a saponified product of a vinyl ester polymer (at least a polymer containing a vinyl ester monomer as a constituent monomer).

[0060] In the laminate of the present invention, as PVA, a substance having a saponification degree of less than 90 mol% is used. With such a PVA having a low saponification degree, the hydrophilicity is slightly suppressed, and by improving the compatibility with P3HB, the adhesion between the paper substrate layer and the first resin layer is further improved, and as a result, the heat sealing property or lamination property of the laminate can be improved. On the other hand, PVA having a saponification degree of more than 90 mol% has a tendency to have a very high hydrophilicity, a reduced compatibility with P3HB, and insufficient adhesion between the paper substrate layer and the resin layer.

[0061] The saponification degree of the above-mentioned PVA may be 89 mol% or less. In addition, it may be 85 mol% or less, 80 mol% or less, or 75 mol% or less. The lower limit is not particularly limited, but is preferably 60 mol% or more, more preferably 65 mol% or more, and further preferably 70 mol% or more. As PVA showing such a saponification degree, a commercial product may be used. The saponification degree of PVA can be measured, for example, by the method specified in JIS K6726.

[0062] In addition, the saponification degree of Kuraray 28-98, which is a completely saponified PVA used in Example 1 of Patent Document 1, is about 98 to 99 mol %, and the saponification degree of Kuraray RS1713, which is a partially saponified ethylene-vinyl acetate copolymer (ethylene-modified PVA) used in Example 9 of the same document, is 92 to 94 mol %, both of which are outside the numerical range of the above-mentioned saponification degree.

[0063] The average degree of polymerization of PVA is not particularly limited, and may be, for example, 100 or more, preferably 200 or more, more preferably 300 or more, and further preferably 500 or more. The upper limit may be, for example, 4000 or less, preferably 3000 or less, more preferably 2000 or less, and further preferably 1000 or less. The average degree of polymerization of PVA can be measured, for example, by the method specified in JIS K6726.

[0064] PVA may have units derived from monomers other than vinyl alcohol and vinyl ester monomers (i.e., materials modified by other monomers). However, since olefin-modified (e.g., ethylene-modified) PVA has a higher lipophilicity, the affinity with the paper substrate may decrease, and the adhesion between the paper substrate layer and the resin layer may decrease. Therefore, it is preferable to use PVA that has not been olefin-modified.

[0065] The content ratio of P3HB and PVA in the first resin layer is set to be within the range of 99.8 / 0.2 to 95.0 / 5.0 of the solid content weight ratio of P3HB / PVA. By using two resins in such a ratio, while achieving the effect of using PVA showing a specific saponification degree, good water resistance of the laminate can also be ensured. In addition, good biodegradability derived from P3HB can be achieved. When the content ratio of PVA is too low, the adhesion between the paper base material layer and the first resin layer decreases, and the heat sealing or lamination of the laminate becomes insufficient. On the contrary, when it is too high, the water resistance of the laminate becomes insufficient and the biodegradability is also reduced.

[0066] The solid content weight ratio of P3HB / PVA is preferably 99.5 / 0.5 to 95.0 / 5.0, more preferably 99.0 / 1.0 to 96.0 / 4.0, further preferably 98.5 / 1.5 to 96.5 / 3.5, and particularly preferably 98.0 / 2.0 to 97.0 / 3.0.

[0067] Within the scope that does not impair the effect of the invention, the first resin layer may contain one or more dispersants or emulsifiers, pH adjusters, inorganic fillers, colorants such as pigments and dyes; odor absorbers such as activated carbon and zeolite; flavors such as vanillin and dextrin; plasticizers, antioxidants, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, lubricants, mold release agents, water repellents, antibacterial agents, sliding improvers, etc. However, these are optional ingredients, and the first resin layer may not contain these ingredients.

[0068] The thickness of the first resin layer is not particularly limited and can be appropriately determined in consideration of the performance and productivity required for the first resin layer. Specifically, it is preferably 0.5 to 30 μm, more preferably 1 to 20 μm, and further preferably 2 to 15 μm. By having such a thickness, the performance of the first resin layer can be fully utilized. In addition, the production cost can be reduced, and the handling and molding of the laminate can be made easier.

[0069] As a method for forming the first resin layer, an extrusion lamination method or a heat lamination method can be used, and the following method is preferably used: a water-based coating liquid prepared by dissolving or dispersing a resin component containing at least P3HB and PVA in a liquid such as water is applied to the surface of a paper substrate, and the first resin layer is formed by heating and drying the liquid (hereinafter sometimes referred to as a "coating method"). In particular, when the first resin layer is directly laminated on the paper substrate layer without passing through other layers, since part of the coating liquid penetrates into the paper substrate layer, it is easy to further improve the adhesion between the paper substrate layer and the first resin layer. From this point of view, it is preferable to use the coating method.

[0070] The above-mentioned water-based coating liquid can be prepared, for example, with reference to International Publication No. 2021 / 075412.

[0071] There is no particular limitation on the method for applying the water-based coating liquid to the paper substrate, and any known method capable of forming a resin layer on the substrate can be appropriately used. Specifically, a spraying method, a spreading method, a slit coating method, an air knife coating method, a roller coating method, a rod coating method, a notched wheel coating method, a blade coating method, a screen printing method, a gravure printing method, etc. can be used. Before applying the water-based coating liquid, a surface treatment step such as the corona treatment can be applied to the paper substrate.

[0072] The drying treatment after coating can be carried out using a known heating method. For example, hot air heating, infrared heating, ultrasonic irradiation, microwave heating, roller heating, hot plate heating, etc. can be mentioned. These can be used alone or in combination of two or more.

[0073] In the drying process after coating, the resin components contained in the first resin layer, especially P3HB as the main resin component, are preferably heated at a temperature at which they can melt to form a film. Therefore, the P3HB in the first resin layer is temporarily melted, and then cooled and solidified, so that the surface of the first resin layer (the surface on the side not facing the paper substrate layer) becomes smooth, and at the same time, the adhesion between the paper substrate layer and the first resin layer is further improved, and the heat sealing property or lamination property can be further improved.

[0074] From the above viewpoints, the heating temperature in the drying treatment after coating is preferably 130° C. or higher, more preferably 140° C. or higher, further preferably 150° C. or higher, and particularly preferably 160° C. or higher. From the viewpoint of avoiding thermal decomposition of P3HB, the upper limit of the heating temperature is preferably 180° C. or lower.

[0075] The heating time in the drying treatment after coating is not particularly limited and can be appropriately set, and can be, for example, about 10 seconds to 10 minutes, preferably about 30 seconds to 5 minutes.

[0076] By drying after coating, the surface of the first resin layer (the surface on the side not facing the paper substrate layer) with increased smoothness can show high gloss. Specifically, for the surface of the first resin layer, the gloss measured at an incident angle of 60° according to "Specular gloss - Determination method" specified in JIS Z 8741:1997 is preferably 5% or more. For a laminate including a first resin layer showing such gloss, the adhesion between the paper substrate layer and the first resin layer is further improved, and the heat sealability or lamination property can be further improved.

[0077] The glossiness value is preferably 7% or more, more preferably 8% or more, further preferably 9% or more, and particularly preferably 10% or more. The upper limit is not particularly limited, and for example, it may be 20% or less, or 15% or less. It should be noted that when the heating temperature is not high enough in the drying process after coating, the glossiness value of the surface of the first resin layer is usually less than 5%.

[0078] The coating amount of the first resin layer is not particularly limited and can be appropriately determined in consideration of the performance required for the first resin layer, productivity, etc. Specifically, the weight per unit area of ​​the first resin layer measured in accordance with JIS P 8124 is preferably 1 to 30 g / m 2 , more preferably 2 to 20 g / m 2, more preferably 3 to 15 g / m 2 When the weight per unit area is within this range, the performance of the first resin layer can be fully exerted. In addition, the production cost can be reduced, and the handling and molding of the laminate can be made easier.

[0079] In the laminate of one embodiment of the present disclosure, the first resin layer may constitute the outermost layer. In this case, the first resin layer may function as a heat seal layer, a water resistant layer, and / or an oil resistant layer. In this embodiment, the thickness of the first resin layer may be 0.5 to 30 μm, preferably 3 to 25 μm, and more preferably 5 to 20 μm as described above.

[0080] The heat seal layer is a layer having heat seal adaptability, specifically, a layer that can be bonded to a bonding object by heating and pressing. The bonding object can be a heat seal layer, a paper substrate layer, or an object made of other materials.

[0081] The laminate of the present disclosure can achieve good heat-sealing properties even at a relatively low heating temperature during heat sealing. Such a heating temperature is not particularly limited, and may be, for example, about 110 to 160°C, preferably 120 to 150°C, and more preferably 125 to 140°C.

[0082] According to a preferred embodiment of the present disclosure, the water-resistant layer is a layer of paper and paperboard defined in JIS P8140:1998, which has a water absorption (Cobb value) of 20 g / m2 when the contact time is 1800 seconds with 90°C warm water. 2 The first resin layer exhibits long-term water resistance to warm water, so the laminated body disclosed in the present invention can be formed into a paper container such as paper tableware for use. The water absorption is preferably 10 g / m 2 Below, more preferably 5g / m 2 the following.

[0083] According to a preferred embodiment of the present disclosure, the oil-resistant layer is a layer having an average Kit number of 10 or more measured at any five points on the surface of the layer according to "Paper and paperboard - Oil release test method - Kit method" specified in JAPAN TAPPI No. 41: 2000. The average Kit number is preferably 11 or more, more preferably 12.

[0084] (Second resin layer)

[0085] In the laminated body of another embodiment of the present disclosure, a second resin layer may be further laminated on the first resin layer. In this embodiment, the paper base material layer, the first resin layer, and the second resin layer are laminated in this order.

[0086] In this embodiment, the first resin layer functions as an adhesion-promoting coating layer between the paper substrate layer and the second resin layer, and the adhesion between the paper substrate layer and the first resin layer is good, so the lamination (lamination strength) between the paper substrate layer and the second resin layer can also be improved. In addition, by providing the second resin layer, a high level of water resistance and oil resistance can be given to the laminate.

[0087] In this embodiment, the first resin layer only needs to have adhesive properties with the paper base layer and the second resin layer. As described above, the thickness of the first resin layer may be 0.5 to 30 μm, preferably 0.7 to 15 μm, and more preferably 1 to 10 μm.

[0088] The second resin layer may be the outermost layer of the laminate, or another layer may be further laminated on the second resin layer.

[0089] The second resin layer preferably contains a biodegradable resin or a biodegradable substance. Based on this, the biodegradability of the entire laminate can be improved. As biodegradable resins that can be used, the resins related to the first resin layer mentioned above can be cited, specifically, in addition to P3HB, aliphatic polyester resins, aliphatic aromatic polyester resins, etc. can be cited.

[0090] From the viewpoint of the affinity between the second resin layer and the first resin layer, it is preferred to contain at least P3HB. Based on this, the adhesion between the first resin layer and the second resin layer can be further improved. However, the second resin layer does not need to contain the above-mentioned PVA.

[0091] The second resin layer preferably contains 50% by weight or more of P3HB, more preferably 70% by weight or more, further preferably 80% by weight or more, and further preferably 90% by weight or more. It may also contain 95% by weight or more. The resin component contained in the second resin layer may be only P3HB, or it may further contain another resin. As the other resin, the above-mentioned biodegradable resin can be used.

[0092] Since the type of P3HB that can be used in the second resin layer is the same as that of P3HB that can be used in the first resin layer, detailed description is omitted. Although not particularly limited, the P3HB that can be used in the second resin layer preferably includes a copolymer containing 3-hydroxybutyrate units and other hydroxyalkanoate units, and is particularly preferably PHBH.

[0093] The second resin layer preferably contains 50% by weight or more of PHBH, more preferably 70% by weight or more, further preferably 80% by weight or more, and further preferably 90% by weight or more. It may also contain 95% by weight or more. The resin component contained in the second resin layer may be only PHBH, or may further contain other resins.

[0094] Since the average content ratio and weight average molecular weight of the constituent monomers related to P3HB that can be used in the second resin layer are the same as those of P3HB that can be used in the first resin layer, detailed description thereof is omitted.

[0095] The second resin layer may contain additives commonly added to resin materials within the scope that does not hinder the effect of the invention. As such additives, for example, there can be cited: colorants such as inorganic fillers, pigments, dyes; odor absorbers such as activated carbon and zeolite; fragrances such as vanillin and dextrin; plasticizers, antioxidants, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, lubricants, release agents, water repellents, antibacterial agents, sliding improvers, etc. As these additives, only one type can be used, or two or more types can be used in combination. However, additives are components that are used arbitrarily, and the second resin layer may not contain these additives. As additives, from the viewpoint of being able to improve the peelability from the pressure-bonded surface of the cooling roller, etc. during the lamination of the second resin layer, it is preferred to use at least one selected from lubricants and inorganic fillers.

[0096] Examples of the lubricant include saturated or unsaturated fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, oleic acid amide, and erucic acid amide; aliphatic amide compounds such as alkylene fatty acid amides such as methylene bisstearic acid amide and methylene bisstearic acid amide; and pentaerythritol.

[0097] The amount of the lubricant in the second resin layer is preferably 0.1 to 2 parts by weight, more preferably 0.2 to 1 part by weight, relative to 100 parts by weight of the total amount of the resin component contained in the second resin layer. By setting the amount to be 0.1 parts by weight or more, the effect of improving the peelability brought about by the lubricant can be obtained. When the amount is 2 parts by weight or less, the problem of the lubricant leaking during crimping and adhering to the crimping surface of the cooling roller, etc. can be suppressed, and long-term continuous processing can be performed.

[0098] Examples of the inorganic filler include talc, calcium carbonate, mica, silica, clay, kaolin, titanium oxide, aluminum oxide, and zeolite. The average particle size of these inorganic fillers is preferably 0.5 μm or more.

[0099] The amount of the inorganic filler in the second resin layer is preferably 0.5 to 5 parts by weight, more preferably 1 to 3 parts by weight, relative to 100 parts by weight of the total amount of the resin component contained in the second resin layer. By setting the amount to be 0.5 parts by weight or more, the peeling property improvement effect brought about by the inorganic filler can be obtained. When the amount is 5 parts by weight or less, the generation of cracks in the second resin layer can be suppressed.

[0100] The thickness of the second resin layer is not particularly limited and can be appropriately determined in consideration of the performance required for the second resin layer, productivity, etc., and can be, for example, about 5 to 100 μm, preferably 10 to 80 μm, and more preferably 20 to 60 μm. The second resin layer is preferably thicker than the first resin layer.

[0101] As a method for forming the second resin layer on the first resin layer, the above-mentioned coating method can be used. However, from the viewpoint of adhesion to the first resin layer, productivity, or the viewpoint of suppressing thermal degradation, it is preferred to form the second resin layer on the surface of the first resin layer by extrusion lamination or thermal lamination.

[0102] As the extrusion lamination method, a general extrusion lamination method can be used. Specifically, a three-layer laminate can be manufactured by extruding a molten resin material from a T-die in a film shape, and then using a cooling roller to press the molten resin material onto the surface of one side of the first resin layer of the laminate while cooling it, and then immediately peeling the resin material from the cooling roller to form a second resin layer.

[0103] When the second resin layer is formed by the extrusion lamination method, the resin temperature immediately after melt extrusion from the tip of the T-die is preferably equal to or higher than the melting point of the resin component contained in the second resin layer and lower than the decomposition temperature of the resin component.

[0104] As the above-mentioned heat lamination method, a general heat lamination method can be used. Specifically, first, a molten resin material is extruded from, for example, a T-die, and a molded film containing the resin material is obtained while being cooled with a cooling roller. Then, the obtained molded film can be pressed onto the surface of the first resin layer side of the laminate with a hot roller or the like, thereby manufacturing a three-layer laminate.

[0105] When the second resin layer is formed by the above-mentioned heat lamination method, when obtaining a molded film constituting the second resin layer, the resin temperature just after melt extrusion from the front end of the T-die is preferably above the melting point of the resin component contained in the second resin layer and below the decomposition temperature of the resin component.

[0106] For the purpose of improving the adhesion between the second resin layer and the first resin layer, the surface of the first resin layer may be subjected to a corona treatment, a flame treatment, an ozone treatment, or the like.

[0107] 〔Molding body〕

[0108] A molded body according to one embodiment of the present disclosure (hereinafter sometimes referred to as "the present molded body") includes the present laminate and has a desired size and shape. The present molded body is formed of a laminate including a first resin layer containing P3HB, and is therefore advantageous in various applications.

[0109] The present molded body is not particularly limited as long as it includes the present laminate, and examples thereof include paper, film, sheet, tube, plate, rod, container (e.g., bottle container), bag, member, etc. From the viewpoint of countermeasures against marine pollution, the present molded body is preferably a bag or bottle container.

[0110] In one embodiment of the present disclosure, the present molded product may be the present laminate itself, or may be a molded product obtained by subjecting the present laminate to secondary processing.

[0111] By performing secondary processing on the present laminate, the present molded body including the same can be preferably used as various packaging container materials such as shopping bags, various bags, food / snack packaging materials, cups, trays, and boxes (in other words, in various fields such as food, cosmetics, electronics, medical treatment, and pharmaceuticals). Since the present laminate includes a resin having high adhesion to a substrate and good heat resistance, it is more preferably used as a container for liquids, especially cups for instant noodles, instant soup, coffee, and other beverages, dishes, lunch boxes, microwaveable foods, and other trays for warm contents.

[0112] The above-mentioned various secondary processing can be carried out by the same method as the existing resin laminated paper or coated paper, that is, using various bag making machines, filling and packaging machines, etc. In addition, it can also be processed by using devices such as paper cup forming machines, punching machines, box making machines, etc. In these processing machines, the bonding method of the present biodegradable laminate can use known techniques, for example, heat sealing method, impulse sealing method, ultrasonic sealing method, high frequency sealing method, hot air sealing method, flame sealing method, etc.

[0113] The heat sealing temperature of the present laminate varies depending on the bonding method. For example, when using a heated heat sealing tester with a sealing strip, the surface temperature of the first resin layer or the second resin layer can usually be set to 180°C or less, preferably 170°C or less, and more preferably 160°C or less. When it is within the above range, the dissolution of the resin near the sealing portion can be avoided, and the film thickness and sealing strength of the appropriate resin layer can be ensured. Since the present laminate can achieve good adhesion even when heat-sealed at low temperatures, the above surface temperature can be 150°C or less, or 140°C or less.

[0114] When a heating heat seal tester having a sealing bar is used, the lower limit of the surface temperature is usually 100° C. or higher, preferably 110° C. or higher, and more preferably 120° C. or higher. Within the above range, appropriate adhesion of the seal portion can be ensured.

[0115] The heat seal pressure of this stack varies depending on the bonding method. For example, with respect to the heat seal pressure of this stack, when a heating heat seal tester with a sealing strip is used, it is usually more than 0.1MPa, preferably more than 0.5MPa. When it is within the above range, it can be ensured that the sealing portion is properly bonded. In addition, when using a heating heat seal tester with a sealing strip, the upper limit of the heat seal pressure is usually less than 1.0MPa, preferably less than 0.75MPa. When it is within the above range, the thin layer of the film thickness of the sealing end can be avoided to ensure the sealing strength.

[0116] In addition, in order to improve the physical properties of the present molded body, a molded body composed of a material different from the present molded body (for example, fibers, threads, ropes, fabrics, knitted fabrics, nonwoven fabrics, paper, films, sheets, tubes, plates, rods, containers, bags, components, foams, etc.) may be compounded. These materials are also preferably biodegradable.

[0117] Preferred aspects of the present disclosure are listed in the following items, but the present invention is not limited to the following items.

[0118] [Project 1]

[0119] A laminate comprising: a paper substrate layer and a first resin layer provided on at least one side of the paper substrate layer, wherein:

[0120] The first resin layer contains a poly(3-hydroxybutyrate) resin and polyvinyl alcohol having a saponification degree of less than 90 mol %,

[0121] The solid content weight ratio of the poly(3-hydroxybutyrate) resin / the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.0.

[0122] [Project 2]

[0123] The laminate according to item 1, wherein

[0124] The poly(3-hydroxybutyrate)-based resin contains a copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units.

[0125] [Item 3]

[0126] The laminate according to item 2, wherein

[0127] The above-mentioned other hydroxyalkanoate unit is a 3-hydroxyhexanoate unit.

[0128] [Item 4]

[0129] The laminate according to any one of items 1 to 3, wherein

[0130] The surface of the first resin layer not facing the paper base layer has a glossiness of 5% or more measured at an incident angle of 60° in accordance with "Specular glossiness - Measurement method" specified in JIS Z 8741:1997.

[0131] [Item 5]

[0132] The laminate according to any one of items 1 to 4, wherein

[0133] The thickness of the first resin layer is 0.5-30 μm.

[0134] [Item 6]

[0135] The laminate according to any one of items 1 to 5, further comprising a second resin layer provided on the first resin layer, wherein

[0136] The second resin layer contains a poly(3-hydroxybutyrate)-based resin.

[0137] [Item 7]

[0138] The laminate according to any one of items 1 to 6, which is used for a packaging material.

[0139] [Item 8]

[0140] The laminate according to any one of items 1 to 6, which is used for a paper container.

[0141] [Item 9]

[0142] A molded body comprising the laminate according to any one of claims 1 to 8.

[0143] [Item 10]

[0144] A method for manufacturing a laminate, comprising:

[0145] A step of applying a water-based coating liquid to at least one side of a paper substrate and drying the liquid to form a first resin layer on the paper substrate, wherein:

[0146] The water-based coating liquid contains a poly(3-hydroxybutyrate) resin and a polyvinyl alcohol having a saponification degree of less than 90 mol %;

[0147] The solid content weight ratio of the poly(3-hydroxybutyrate) resin / the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.0.

[0148] [Item 11]

[0149] The manufacturing method according to item 10, wherein:

[0150] The first resin layer has a weight per unit area of ​​1 to 30 g / m2 as measured in accordance with JIS P 8124. 2 .

[0151] [Item 12]

[0152] The manufacturing method according to item 10 or 11, wherein:

[0153] The drying is performed by heating to a temperature of 130 to 180°C.

[0154] [Item 13]

[0155] The manufacturing method according to any one of items 10 to 12, further comprising: a step of forming a second resin layer on the first resin layer, wherein

[0156] The second resin layer contains a poly(3-hydroxybutyrate)-based resin.

[0157] [Item 14]

[0158] The manufacturing method according to item 13, wherein:

[0159] The second resin layer is formed by extrusion lamination or heat lamination.

[0160] Example

[0161] Hereinafter, the present invention will be specifically described by way of examples, but the technical scope of the present invention is not limited by these examples.

[0162] (Evaluation method for film-forming property of coated paper)

[0163] In order to evaluate the film-forming property of the coating layer, the glossiness of the coating layer surface was measured at an incident angle of 60° using a gloss meter (IG-320 manufactured by HORIBA) according to "Specular glossiness - Measurement method" specified in JIS Z 8741: 1997. The higher the glossiness value, the higher the smoothness of the coating layer surface.

[0164] (Evaluation method for water resistance of coated or laminated paper)

[0165] The water absorption (Cobb value) was measured by contacting any two points of the coating layer or laminated layer surface with 90°C hot water for 1800 seconds in accordance with "Paper and paperboard - Test method for water absorption - Cobb method" specified in JIS P 8140:1998.

[0166] The average value of the water absorption (Cobb value) measured at two points was adopted as the water resistance value, and the water resistance was evaluated according to the following criteria: When the evaluation was ◎, ○ or △, it was judged that there was no problem in practical use.

[0167] [Evaluation criteria]

[0168] ◎: The average water absorption (Cobb value) is 5g / m 2 the following.

[0169] ○: The average water absorption (Cobb value) exceeds 5 g / m 2 And 10g / m 2 the following.

[0170] △: The average water absorption (Cobb value) exceeds 10 g / m 2 And 20g / m 2 the following.

[0171] ×: The average water absorption (Cobb value) exceeds 20 g / m 2 .

[0172] (Evaluation method for oil resistance of coated or laminated paper)

[0173] The Kit number was measured at five random points on the surface of the coating layer or laminated layer in accordance with "Paper and paperboard - Oiliness test method - Kit method" specified in JAPAN TAPPI No. 41: 2000.

[0174] The average value of the Kit number of the five measured points was adopted as the value of oil resistance, and the oil resistance was evaluated according to the following criteria. When the evaluation was ◎, ○, or △, it was judged that there was no problem in practical use.

[0175] [Evaluation criteria]

[0176] ◎: The average value of the kit number is 12.

[0177] 0:The average value of kit number is 11 or more and less than 12.

[0178] △: The average value of the kit number is 10 or more and less than 11.

[0179] ×: The average value of the kit number is less than 10.

[0180] (Evaluation method of adhesion between coating layer and paper substrate)

[0181] A transparent tape (25 mm wide) was pasted on the surface of the coating layer, and a rubber roller (130 mm wide and 1.8 kg in weight) was moved back and forth on the transparent tape 5 times by its own weight to make the transparent tape and the surface of the coating layer adhere closely.

[0182] Immediately thereafter, the transparent tape was peeled off with force, and the ratio of the area where the coating layer was peeled off from the surface of the paper substrate and attached to the transparent tape (surface damage area) to the area of ​​the attached transparent tape was calculated, or the ratio of the area where the paper substrate was damaged and a part of the paper substrate was attached to the transparent tape together with the coating layer (the area of ​​the internal damage of the paper substrate) to the area of ​​the attached transparent tape was calculated. The adhesion to the paper substrate was evaluated by the following criteria. When the evaluation was ◎, 0 or △, it was judged that there was no problem in practical use.

[0183] In addition, when there was a difference between the evaluation of the ratio of the area where the coating layer was peeled and the ratio of the area where the paper substrate was damaged, the stricter evaluation was adopted.

[0184] [Evaluation criteria]

[0185] ◎: The ratio of the coating layer peeling area is less than 5%,

[0186] Or the ratio of the damaged area of ​​the paper substrate is 95% or more.

[0187] ○: The ratio of the area where the coating layer is peeled off is 5% or more and less than 10%,

[0188] Alternatively, the ratio of the damaged area of ​​the paper substrate is 90% or more and less than 95%.

[0189] △: The ratio of the area where the coating layer peels off is 10% or more and less than 30%,

[0190] Alternatively, the ratio of the damaged area of ​​the paper substrate is 70% or more and less than 90%.

[0191] ×: The ratio of the area where the coating layer peeled off was 30% or more,

[0192] Or the proportion of the damaged area of ​​the paper substrate is less than 70%.

[0193] (Evaluation method for heat sealability of coated paper)

[0194] Two 25 mm wide strips were cut from the obtained coated paper, and the coated layers were placed in contact with each other. The strips were pressed at a temperature of 130°C and a pressure of 2 kgf / cm 2 , heat sealing was performed at a pressurization time of 0.5 seconds.

[0195] In order to measure the heat seal strength of the test piece, an Autograph was used to clamp the two sides of the paper substrate with a clamp, and the peeled portion when peeled 180° was visually observed. The heat sealability was evaluated according to the following criteria. If the evaluation was 0 or △, it was judged that there was no problem in practical use.

[0196] [Evaluation criteria]

[0197] ○: Peeling occurred in the paper substrate (the paper substrate was damaged).

[0198] △: Most of the peeling occurred in the paper substrate (the paper substrate was damaged).

[0199] ×: The paper substrate was not damaged, but peeling occurred between the paper substrate and the coating layer or between the coating layers.

[0200] (Evaluation method for lamination properties of laminated paper)

[0201] A 25 mm wide strip was cut from the obtained laminated paper (the unlaminated portion remained), and in order to evaluate the lamination property of the test piece, an Autograph was used, and the unlaminated portion of the paper substrate and the unlaminated portion of the film were clamped by a clamp, respectively, and the peeled portion when peeled 180° was visually observed, and the lamination property was evaluated according to the following criteria. When the evaluation was 0, it was judged that there was no problem in practical use.

[0202] [Evaluation criteria]

[0203] ○: Cohesive failure of the paper occurred, and paper fibers adhered to the film side.

[0204] △: Cohesive failure of the paper occurred, and paper fibers adhered to a part of the film side.

[0205] ×: The paper did not undergo cohesive failure, and there was no resistance on the film side, so the paper could be easily peeled off.

[0206] (Evaluation of biodegradability of coating layer components)

[0207] The biodegradability of the dry powder of the coating component passed through a 100-mesh filter in seawater was calculated from the oxygen consumption of the bacteria using a BOD measuring machine (OXITOP series, manufactured by Central Chemical) at an incubator temperature of 30±1°C (with stirring) for 180 days, and was evaluated using the following criteria.

[0208] [Evaluation criteria]

[0209] ○: Biodegradability is 90% or more within 180 days

[0210] ×: Biodegradability is less than 90% within 180 days

[0211] (Preparation of an aqueous suspension containing PHBH isolated from microorganisms)

[0212] First, Ralstonia eutropha (formerly known as Alcaligenes eutrophus AC32 (Deposit No. FERM BP-6038)) into which a 3-hydroxyalkanoic acid copolymer synthase gene derived from Aeromonas caviae was introduced was cultured according to the method described in J. Bacteriol., 179, pp. 4821-4830 (1997), and a bacterial cell containing about 67% by weight of PHBH was obtained. In this PHBH, the composition ratio of repeating units (composition ratio of 3-hydroxybutyrate unit / 3-hydroxyhexanoate unit) was 89 / 11 (mol / mol).

[0213] Next, the paste-like bacterial cells were separated from the culture solution by centrifugation (5000 rpm, 10 min). Water was added to the bacterial cells to prepare a suspension of 75 g of dry bacterial cells / L, and an aqueous sodium hydroxide solution was added as an alkali. The bacterial cell constituent substances other than PHBH were solubilized by stirring and physical disruption while maintaining pH 11.7, and centrifugation was performed (3000 rpm, 10 min) to obtain a precipitate. The precipitate was further washed with water to separate PHBH with a weight average molecular weight of about 260,000, a 3HH molar fraction of 11%, and a purity of 91%, and a suspension containing 75 g / L of PHBH was obtained.

[0214] The suspension was placed in a stirring tank equipped with a pH electrode and kept warm at 70°C. The pH electrode was connected to the LABO-Controller-MDL-6C model manufactured by Maru-Ryo Bioengineering Co., Ltd. and set to: when the pH is below the set value, the Perista pump works and an aqueous sodium hydroxide solution is added to the suspension until the set value is reached. The pH of the LABO-Controller was set to 10, and 30% hydrogen peroxide was added to the suspension so that the hydrogen peroxide concentration was 5% by weight relative to the weight of the polymer (0.375% by weight relative to the weight of the suspension), and stirred for 1 hour. The suspension was then washed with water twice by centrifugation and further washed with methanol twice. As an antiseptic treatment, 30% hydrogen peroxide was further added to the solid content (PHBH) of the aqueous suspension so that the hydrogen peroxide concentration was 0.1% by weight. Through the above treatment, an aqueous suspension (A) with a PHBH concentration of 52% by weight was obtained. The protein content of the aqueous suspension (A) was 1500 ppm in the solid content, and the purity of PHBH was 99.8% or more.

[0215] [Example 1]

[0216] (Preparation of coating liquid 1 for coating layer)

[0217] A binder (polyvinyl alcohol, manufactured by Kuraray: L-10, saponification degree 71.5-73.5 mol%) was mixed with the PHBH aqueous suspension (A) to a solid content weight ratio of 98.0 / 2.0, and water was further added and stirred to prepare a coating layer coating liquid 1 having a total solid content concentration of PHBH and the binder of 40 wt%.

[0218] (Production of coated paper)

[0219] On paper substrate (weight per unit area 50g / m 2 On one side of the single-sided glossy paper) was coated with the coating layer coating liquid 1 by a rod coating method so that the weight per unit area was 10.0 g / m 2 (thickness 8 μm), and dried at a drying temperature of 160° C. for 2 minutes to obtain a coated paper.

[0220] [Example 2]

[0221] A coated paper was obtained in the same manner as in Example 1 except that the solid content weight ratio of the PHBH aqueous dispersion and the binder in the coating liquid 1 for the coating layer was changed to 95.0 / 5.0.

[0222] [Example 3]

[0223] A coated paper was obtained in the same manner as in Example 1 except that the solid content weight ratio of the PHBH aqueous dispersion and the binder in the coating layer coating liquid 1 was changed to 99.5 / 0.5.

[0224] [Example 4]

[0225] (Preparation of coating liquid 2 for coating layer)

[0226] A binder (polyvinyl alcohol, manufactured by Kuraray: 5-74, saponification degree 72.5-74.5 mol %) was mixed into the PHBH aqueous suspension (A) so that the solid content weight ratio was 98.0 / 2.0, and water was further added and stirred to prepare a coating layer coating liquid 2 having a total solid content concentration of PHBH and the binder of 40 wt %.

[0227] (Production of coated paper)

[0228] A coated paper was obtained in the same manner as in Example 1 except that the coating liquid 1 for coating layer was changed to the coating liquid 2 for coating layer.

[0229] [Example 5]

[0230] A coated paper was obtained in the same manner as in Example 4 except that the solid content weight ratio of the PHBH aqueous dispersion and the binder in the coating liquid 2 for coating layer was changed to 95.0 / 5.0.

[0231] [Example 6]

[0232] (Preparation of coating liquid 3 for coating layer)

[0233] A binder (polyvinyl alcohol, manufactured by Kuraray: 5-88, saponification degree 86.5-89.0 mol %) was mixed into the PHBH aqueous suspension (A) so that the solid content weight ratio was 98.0 / 2.0, and water was further added and stirred to prepare a coating layer coating liquid 3 having a total solid content concentration of PHBH and the binder of 40 wt %.

[0234] (Production of coated paper)

[0235] A coated paper was obtained in the same manner as in Example 1 except that the coating liquid 1 for coating layer was changed to the coating liquid 3 for coating layer.

[0236] [Example 7]

[0237] A coated paper was obtained in the same manner as in Example 6 except that the solid content weight ratio of the PHBH aqueous dispersion and the binder in the coating liquid 3 for the coating layer was changed to 95.0 / 5.0.

[0238] [Comparative Example 1]

[0239] (Preparation of coating liquid 4 for coating layer)

[0240] Water was added to the PHBH aqueous suspension (A), and the mixture was stirred to prepare a coating liquid 4 for a coating layer having a solid content concentration of 40% by weight.

[0241] (Production of coated paper)

[0242] A coated paper was obtained in the same manner as in Example 1 except that the coating liquid 1 for coating layer was changed to the coating liquid 4 for coating layer.

[0243] [Comparative Example 2]

[0244] A coated paper was obtained in the same manner as in Example 1 except that the solid content weight ratio of the PHBH aqueous dispersion and the binder in the coating liquid 1 for the coating layer was changed to 90.0 / 10.0.

[0245] [Comparative Example 3]

[0246] (Preparation of coating liquid 5 for coating layer)

[0247] A binder (polyvinyl alcohol, manufactured by Kuraray Co., Ltd.: 5-98, saponification degree 98.0-99.0 mol %) was mixed into the PHBH aqueous suspension (A) so that the solid content weight ratio was 98.0 / 2.0, and water was further added and stirred to prepare a coating layer coating liquid 5 having a total solid content concentration of PHBH and the binder of 40 wt %.

[0248] (Production of coated paper)

[0249] A coated paper was obtained in the same manner as in Example 1 except that the coating liquid 1 for coating layer was changed to the coating liquid 5 for coating layer.

[0250] The coated papers obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were evaluated for film forming properties, water resistance, oil resistance, adhesion between the coating layer and the paper substrate, and heat sealing properties by the above-mentioned methods. The results are shown in Table 1.

[0251]

[0252] As shown in Table 1, the coated papers of Examples 1 to 7 have coating layers containing P3HB and PVA satisfying a specific saponification degree at a specific ratio, good water resistance, high adhesion between the coating layer and the paper substrate, and good heat sealing properties.

[0253] On the other hand, the coating layer of the coated paper of Comparative Example 1 did not contain PVA, the adhesion between the coating layer and the paper substrate was low, and the heat sealing property was also insufficient.

[0254] Although the coating layer of the coated paper of Comparative Example 2 contains PVA satisfying a specific saponification degree, its content ratio is high and water resistance is insufficient. In addition, due to the high content ratio of PVA, the biodegradability of the coating layer is also reduced.

[0255] The PVA contained in the coating layer of the coated paper of Comparative Example 3 did not satisfy the specified saponification degree, and the adhesion between the coating layer and the paper substrate was slightly low, and the heat sealing property was insufficient.

[0256] [Example 8]

[0257] (Production of Laminated Body by Extrusion Lamination Method)

[0258] In addition to changing the paper substrate to a unit area weight of 200g / m 2 The solid content concentration of the coating liquid 1 for the coating layer was changed to 25% by weight, and the coating amount of the coating liquid 1 for the coating layer was changed to a dry weight per unit area of ​​3.0 g / m 2 A coated paper with a first resin layer was obtained in the same manner as in Example 1 except that the thickness was 2.5 μm.

[0259] As preparation for the second resin layer, PHBH powder (weight average molecular weight 650,000, PHBH powder with a composition ratio of 3-hydroxybutyrate unit / 3-hydroxyhexanoate unit of 85 / 15 (mol / mol)) (100 parts by weight) was dry-blended with behenic acid amide (0.2 parts by weight) and pentaerythritol (1.0 parts by weight), and the mixture was melt-kneaded and extruded in the form of strands using a twin-screw extruder at a set temperature of 150° C. and a screw speed of 100 rpm, and solidified and cut into pellets by passing through warm water at 40° C.

[0260] Next, using a single-screw extruder equipped with a T-die, the conditions were adjusted so that the resin temperature directly below the die was 175°C, the obtained pellets were extruded, and a second resin layer was laminated with a thickness of 30 μm on the first resin layer of the coated paper with the first resin layer prepared above, thereby obtaining a laminated paper comprising a stack of the first resin layer and the second resin layer.

[0261] [Example 9]

[0262] A laminated paper was obtained in the same manner as in Example 8 except that the solid content weight ratio of the PHBH aqueous dispersion and the adhesive in the coating liquid 1 for the coating layer was changed to 95.0 / 5.0.

[0263] [Example 10]

[0264] The coating amount of the coating liquid 1 for the coating layer was changed to a dry weight per unit area of ​​1.0 g / m 2 A laminated paper was obtained in the same manner as in Example 8 except that (thickness: 0.8 μm).

[0265] [Example 11]

[0266] A laminated paper was obtained in the same manner as in Example 8 except that the coating liquid 3 for coating layer was used instead of the coating liquid 1 for coating layer.

[0267] [Example 12]

[0268] A laminated paper was obtained in the same manner as in Example 11 except that the solid content weight ratio of the PHBH aqueous dispersion and the adhesive in the coating liquid 3 for the coating layer was changed to 95.0 / 5.0.

[0269] [Example 13]

[0270] (Manufacturing of laminated body by thermal lamination method)

[0271] The same operation as in Example 8 was carried out to obtain a coated paper with a first resin layer.

[0272] As the preparation of the second resin layer, the same as used in Example 8, behenic acid amide (0.2 parts by weight) and pentaerythritol (1.0 parts by weight) were dry-blended with PHBH powder (100 parts by weight), melt-kneaded using a twin-screw extruder at a set temperature of 150° C. and a screw speed of 100 rpm, and extruded in the form of strands, and solidified by passing through warm water at 40° C. and cut into pellets.

[0273] Next, the obtained pellets were extruded using a single-screw extruder equipped with a T-die, and taken up by a cooling roll set at 60° C., thereby obtaining a film molded body having a thickness of 30 μm.

[0274] Thereafter, the paper side is clamped in a manner such that the paper surface side contacts the heating roller and the film side contacts the cooling roller, and the conditions are adjusted so that the surface temperature of the film molding is 170°C. The film molding is heat-laminated on the first resin layer of the coated paper having the first resin layer, thereby obtaining a laminated paper containing the above-mentioned film molding as the second resin layer.

[0275] [Comparative Example 4]

[0276] A laminated paper was obtained in the same manner as in Example 8 except that the coating liquid 1 for coating layer was used in place of the coating liquid 4 for coating layer.

[0277] [Comparative Example 5]

[0278] A laminated paper was obtained in the same manner as in Example 8 except that the coating liquid 1 for coating layer was used instead of the coating liquid 5 for coating layer.

[0279] [Comparative Example 6]

[0280] A laminated paper was obtained in the same manner as in Comparative Example 5 except that the solid content weight ratio of the PHBH aqueous dispersion and the adhesive in the coating liquid 5 for coating layer was changed to 95.0 / 5.0.

[0281] The film forming properties, water resistance, oil resistance, and lamination properties of the laminated papers obtained in Examples 8 to 13 and Comparative Examples 4 to 6 were evaluated by the above-mentioned methods.

[0282]

[0283] As can be seen from Table 2, in the laminated papers of Examples 8 to 13, which are laminates comprising a first resin layer and a second resin layer, the first resin layer contains PVA satisfying a specific saponification degree at a specific ratio and has good lamination properties.

[0284] On the other hand, the first resin layer of the laminated paper of Comparative Example 4 did not contain PVA, and thus the lamination properties were insufficient.

[0285] In the laminated papers of Comparative Examples 5 and 6, the PVA contained in the first resin layer did not satisfy the specific saponification degree, and the lamination properties were insufficient.

[0286] (Reference example)

[0287] In the preparation of the coated paper with the first resin layer, the same operation as in Example 8 was performed except that the drying temperature of the first resin layer was set to 80°C, 100°C, 120°C, 140°C, 160°C or 180°C for 2 minutes to obtain the coated paper with the first resin layer. The 60° glossiness of the coating layer surface of the obtained coated paper was measured by the above method. The results are shown in Table 3.

[0288]

[0289] As shown in Table 3, when the drying temperature of the coating layer is 80-120°C, the glossiness of the coating layer hardly changes. When the temperature is increased to 140°C or higher, the glossiness increases as the temperature rises. This is believed to be because the PHBH in the coating layer melts due to heating during drying, and then solidifies due to cooling, which improves the smoothness of the coating layer surface.

[0290] In addition, heating during drying causes the PHBH in the coating layer to melt, thereby improving the adhesion, heat sealing and lamination properties between the coating layer and the paper substrate.

Claims

1. A laminate comprising: Paper substrate layer, and The first resin layer provided on at least one side of the paper substrate layer, wherein The first resin layer contains a poly(3-hydroxybutyrate) resin and polyvinyl alcohol having a saponification degree of less than 90 mol %, The solid content weight ratio of the poly (3-hydroxybutyrate) resin to the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.

0.

2. The laminate according to claim 1, wherein The poly(3-hydroxybutyrate)-based resin contains a copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units.

3. The laminate according to claim 2, wherein: The other hydroxyalkanoate unit is a 3-hydroxyhexanoate unit.

4. The laminate according to any one of claims 1 to 3, wherein The glossiness of the surface of the first resin layer not facing the paper base layer measured at an incident angle of 60° in accordance with "Specular glossiness-Measurement method" specified in JIS Z 8741:1997 is 5% or more.

5. The laminate according to any one of claims 1 to 3, wherein The thickness of the first resin layer is 0.5-30 μm.

6. The laminate according to any one of claims 1 to 3, further comprising a second resin layer provided on the first resin layer, wherein The second resin layer contains a poly(3-hydroxybutyrate)-based resin.

7. The laminate according to any one of claims 1 to 3, which is used for packaging materials.

8. The laminate according to any one of claims 1 to 3, which is used for a paper container. 9 . A molded product comprising the laminate according to claim 1 .

10. A method for manufacturing a laminate, the method comprising: A step of applying a water-based coating liquid to at least one side of a paper substrate and drying the coating liquid to form a first resin layer on the paper substrate, wherein: The water-based coating liquid contains a poly(3-hydroxybutyrate) resin and polyvinyl alcohol having a saponification degree of less than 90 mol %, The solid content weight ratio of the poly (3-hydroxybutyrate) resin to the polyvinyl alcohol is 99.8 / 0.2 to 95.0 / 5.

0.

11. The manufacturing method according to claim 10, wherein: The first resin layer has a unit area weight of 1 to 30 g / m2 as measured according to JIS P 8124. 2 .

12. The manufacturing method according to claim 10 or 11, wherein: The drying is performed by heating to a temperature of 130 to 180°C.

13. The manufacturing method according to claim 10 or 11, further comprising: a step of forming a second resin layer on the first resin layer, wherein: The second resin layer contains a poly(3-hydroxybutyrate)-based resin.

14. The manufacturing method according to claim 13, wherein: The second resin layer is formed by extrusion lamination or heat lamination.

Citation Information

Patent Citations

  • Biodegradable polyester resin composition

    WO2013147139A1

  • Polyester film for polarizer protection, polarizing plate and liquid crystal display device

    CN104520738A

  • Biodegradable composite material

    JP1990222421A

  • Coated paper

    WO2021256381A1